Determinants of Risk Behaviour in Livestock Development Programs: Evidence from South Africa’s Kaonafatso Yadikgomo (Kyd) Scheme - Ngarava, Saul; Mushunje, Abbyssinia; Taruvinga, Amon; Mukarumbwa, Peter; Tatsvarei, Simbarashe; Megbowon, Ebenezer T (Journal of Economics and Behavioral Studies, 2018)
Risk plays a significant role in input use decisions and production of output in agricultural production. Understanding farmer risk attitudes and their responses to risk is significant in designing effective intervention programmes. Few studies have tried to identify how the introduction of a livestock programme has tended to influence farmer risk profile. The objective of the study was to highlight the determinants of risk behaviour in participants of a livestock development programme. The study was carried out in KwaZulu-Natal (KZN) Province of South Africa, utilising a purposive sample of 164 respondents who are part of the Kaonafatso Yadikgomo (KYD) Scheme. The cross-sectional survey collected data pertaining to the risk attitudes of the livestock farmers from an attitudinal scale as well as socio-economic and farm biophysical characteristics. Descriptive statistics and multiple linear regression were used to analyse the data. The results show that the livestock farmers were risk loving, with the risk attitude being influenced by the age of household head, monthly household income and experience in rearing cattle at the ð‘ < 0.1 level. Furthermore, the source of income, herd size, reason for slaughtering cattle distance to the nearest water source and access to a dip tank had significant influence of attitude towards risk at the ð‘ < 0.05 level. The study concludes that being part of a livestock development programme tends inflto uence the risk attitudes of the participants as the determinants were against a priori expectations.